Brucella peritonitis and leucocytoclastic vasculitis due to Brucella melitensis - Dizbay,Murat (2007)
Brucellosis is a multisystemic disease that rarely leads to a fatal outcome. While reticuloendothelial system organs are mostly affected, peritonitis and posthepatitic cirrhosis are also complications of brucellosis, though they are very rare. Brucella spp. can also trigger immunological reactions. We report a case of brucellosis with peritonitis, renal failure and leucocytoclastic vasculitis caused by Brucella melitensis, which led to a fatal outcome. Brucellosis should be considered in the differential diagnosis of vasculitic diseases, especially in endemic areas.